2018
DOI: 10.1186/s12877-018-0775-6
|View full text |Cite
|
Sign up to set email alerts
|

Biological clocks and physical functioning in monozygotic female twins

Abstract: BackgroundBiomarkers of biological aging – DNA methylation age (DNAm age) and leukocyte telomere length (LTL)– correlate strongly with chronological age across the life course. It is, however, unclear how these measures of cellular wear and tear are associated with muscle strength and functional capacity, which are known to decline with older age and are associated with mortality. We investigated if DNAm age and LTL were associated with body composition and physical functioning by examining 48 monozygotic twin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 40 publications
3
20
1
Order By: Relevance
“…In addition, measures of obesity such as BMI and waist circumference are shown to be associated with accelerated epigenetic aging ( Grant et al, 2017 ; Horvath et al, 2014 ). How-ever, such a correlation was not observed in other studies ( Nevalainen et al, 2017 ; Sillanpaa et al, 2018 ), and Grant et al (2017) did not find a significant correlation to their 7 diabetesrelated phenotypes. The epigenetic clocks predict all-cause mortality in a variety of human cohorts ( Chen et al, 2016 ; Christensen et al, 2016; Perna et al, 2016 ; Levine et al, 2018 ; Marioni et al, 2018 ).…”
Section: Epigenetic Clocksmentioning
confidence: 55%
See 1 more Smart Citation
“…In addition, measures of obesity such as BMI and waist circumference are shown to be associated with accelerated epigenetic aging ( Grant et al, 2017 ; Horvath et al, 2014 ). How-ever, such a correlation was not observed in other studies ( Nevalainen et al, 2017 ; Sillanpaa et al, 2018 ), and Grant et al (2017) did not find a significant correlation to their 7 diabetesrelated phenotypes. The epigenetic clocks predict all-cause mortality in a variety of human cohorts ( Chen et al, 2016 ; Christensen et al, 2016; Perna et al, 2016 ; Levine et al, 2018 ; Marioni et al, 2018 ).…”
Section: Epigenetic Clocksmentioning
confidence: 55%
“…However, the Horvath clock was not associated with cognitive decline in monozygotic twins ( Starnawska et al, 2017 ). Frailty ( Breitling et al, 2016 ) and frailty outcomes such as grip strength ( Sillanpaa et al, 2018 ) were associated with epigenetic age acceleration; however, standing balance and chair-rise time were not correlated to accelerated epigenetic aging ( Simpkin, Suderman, & Howe, 2017 ). Accelerated epigenetic aging is observed in individuals with Werner’s syndrome who exhibit many signs of accelerated aging ( Maierhofer et al, 2017 ); however, decelerated aging observed in Syndrome X patients is not correlated to changes in the epigenetic clock ( Walker et al, 2015 ).…”
Section: Epigenetic Clocksmentioning
confidence: 99%
“…Currently, about 2000 DNA samples from individuals in the twin cohorts have been analyzed by Illumina HumanMethylation 450k or EPIC BeadChip. In comparison to telomeres, DNA methylation age may be more closely associated with physical functioning phenotypes in older people (Sillanpää et al, 2018). Quantitative genetic modeling in older and younger FTC revealed that the relative contribution of nonshared environmental factors was larger among older compared with younger twin-pairs (Sillanpää et al, 2019).…”
Section: Biological Aging Clocks and Physical Activity And Functioningmentioning
confidence: 97%
“…Based on information in the section above, developing a proxy measure of biological aging for humans still requires work but is a very dynamic and promising area of investigation with strong potential for translation. Some of the measures described-namely mitochondrial function, DNA methylation, and, to a lesser extent, cellular senescence and autophagy-are ready to be implemented based on several epidemiological studies, although refinements are always possible Choi et al, 2016;Cohen, Morissette-Thomas, Ferrucci, & Fried, 2016;Jylhävä, Pedersen, & Hägg, 2017;Jylhävä et al, 2014;Kananen et al, 2016;Kent & Fitzgerald, 2016;Kim & Jazwinski, 2015;Levine et al, 2018;Li et al, 2018;Marioni et al, 2019;Marttila et al, 2015;Putin et al, 2017;Sillanpää et al, 2018). Measures of telomere length are hampered by noise and wide longitudinal variations that cannot be explained by health events and at this stage are not useful for measuring biological age (Arai et al, 2015;Jodczyk, Fergusson, Horwood, Pearson, & Kennedy, 2014;Tomaska & Nosek, 2009).…”
Section: Connec Ting the B I Ology Of Ag Ing With Ag E-a Sso Ciatedmentioning
confidence: 99%